AQP4 knockout promotes neurite outgrowth via upregulating GAP43 expression in infant rats with hypoxic‐ischemic brain injury. Issue 3 (19th August 2022) - Dan, Qi‐Qin; Ma, Zheng; Tan, Ya‐Xin; Visar, Belegu; Chen, Li
Abstract: Neonatal hypoxic‐ischemic encephalopathy (NHIE) induces severe cerebral damage and neurological dysfunction, with seldom effective therapy. Aquaporin‐4 (AQP4) is involved in aggravating brain damage induced by NHIE. This study aimed to investigate the role of AQP4 underlying the pathogenesis of NHIE. Neonatal Sprague–Dawley rats were used to establish neonatal hypoxic‐ischemic (HI) models, and the expression of AQP4 in the cortex, hippocampus, and lung tissues was detected by real‐time quantitative polymerase chain reaction as well as Western blot. Primary cortical neurons were cultured for the oxygen‐glucose deprivation (OGD) model, and siRNA was used to silence the expression of AQP4. Immunostaining of Tuj1 was performed to observe the axonal growth. CRISPER/Cas9 technology was used to knock out AQP4. The results demonstrated that AQP4 was upregulated in the cortex, hippocampus, and lung tissues in neonatal rats with HI and OGD neurons. Besides, silencing AQP4 promoted axonal growth of OGD neurons, and AQP4 knockout notably improved long‐term neurobehavioral impairment. Furthermore, GAP43 was found closely correlated with AQP4 via GeneMANIA prediction. Significant downregulation of GAP43 was induced in OGD neurons, while AQP4 knockout markedly upregulated its expression in rats. This indicated that the depletion of AQP4 may enhance axonal regeneration and promote the long‐term neurobehavioral recovery associated with the upregulation of GAP43 expression. Abstract : Neonatal Sprague–Dawley rats (7 days old) were applied to establish hypoxic‐ischemic (HI) models; moreover, siRNA and CRISPER‐/Cas9‐mediated gene‐editing technologies were then employed to explore the role of AQP4 in the neurological damages at 24 h after HI in vitro and in vivo. The results revealed that silencing AQP4 could promote the outgrowth of the length in oxygen‐glucose deprivation (OGD) neurons. Moreover, AQP4‐knockout could notably improve long‐term neurobehavioral impairment compared with AQP4‐wild type 1 month after HI reflected by the tests of neurological severity score, water maze, and Y‐maze. Furthermore, growth‐associated protein‐43 (GAP43) was closely correlated with AQP4 in both pathway and co‐expression channels via GeneMANIA prediction. As expected, OGD induced significant downregulation of GAP43, while AQP4 knockout could markedly upregulate its expression. These indicated that AQP4 silencing could enhance axon regeneration and promote long‐term neurobehavioral recovery after HI; the underlying mechanism was associated with GAP43 upregulation.